Comparative Study of Toluene and Hexane Adsorption on Activated Carbons From Gas and Liquid Phase. Enthalpy and Isotherms - Hernández-Monje, Diana; Giraldo, Liliana; Moreno-Piraján, Juan Carlos (Frontiers in Environmental Chemistry, 2020)
Activated carbons with different chemical and textural properties were used to carry out the adsorption of toluene and hexane from gas phase and from liquid phase for toluene-hexane solutions where toluene was used as a solute and hexane as the solvent, complementing the process with the evaluation of the immersion enthalpy for the pure components and toluene-hexane mixtures at different molar fractions. The adsorption capacities for the gas phase were between 3.40 mmol g-1 and 0.05 mmol g-1, being higher for toluene because of the π-π interaction with the solid; when evaluating the liquid phase, the adsorption capacities were 0.24 and 0.74 mmol g-1, where the adsorption of toluene decreased compared to the gas phase because of the solute-solute, solvent-solvent, solute-solvent interaction. The immersion enthalpies for the pure solvents were between -40.87 J g-1 and -126.10 J g-1 being higher also for toluene confirming a greater interaction compared to hexane; for the mixtures, immersion enthalpy was higher than hexane enthalpies, but lower than toluene enthalpies with values between -59.79 J g-1 and -107.95 J g-1. It was found that there was a greater interaction between the sample with a lower content of acid groups and a greater surface area with toluene due to the high electron density of carbon and London-type as π- π interactions with the aromatic compound. For mixtures, hexane decreased the adsorption capacity and interaction with respect to toluene because there was competition for adsorption sites and subsequent displacement of hexane molecules when the amount of toluene on the surface increased.